2017
DOI: 10.1002/ecs2.1921
|View full text |Cite
|
Sign up to set email alerts
|

A fine‐scale U.S. population estimate of a montane spruce–fir bird species of conservation concern

Abstract: Citation: Hill, J. M., and J. D. Lloyd. 2017. A fine-scale U.S. population estimate of a montane spruce-fir bird species of conservation concern. Ecosphere 8(8):e01921. 10. 1002/ecs2.1921 Abstract. Bicknell's Thrush (Catharus bicknelli) is one of the most range-restricted bird species in North America. In the United States (U.S.), it occurs only in the disturbed montane forests of fir (Abies balsamea) and spruce (Picea spp.) in the northeastern states of New York, Vermont, New Hampshire, and Maine. Climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Recent changes in passerine distributions and abundances have been observed occurring across latitude and elevation gradients across the world (Auer & King, ; Hickling, Roy, Hill, Fox, & Thomas, ; Parmesan, ; Parmesan & Yohe, ; Tingley, Monahan, Beissinger, & Moritz, ). In the Northeastern United States, there is evidence that populations of high‐elevation montane bird species have been declining for decades (Hill & Lloyd, ; King, Lambert, Buonaccorsi, & Prout, ; Lambert, King, Buonaccorsi, & Prout, ; Studds, McFarland, et al, ), including state‐level extirpation of high‐elevation endemic species (Rimmer & Mcfarland, ). Moreover, in the White Mountains of New Hampshire, low‐elevation birds have been shown to have shifted their range over 100 m upslope while high‐elevation birds have shifted their ranges downslope over the same 19 year period (DeLuca & King, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent changes in passerine distributions and abundances have been observed occurring across latitude and elevation gradients across the world (Auer & King, ; Hickling, Roy, Hill, Fox, & Thomas, ; Parmesan, ; Parmesan & Yohe, ; Tingley, Monahan, Beissinger, & Moritz, ). In the Northeastern United States, there is evidence that populations of high‐elevation montane bird species have been declining for decades (Hill & Lloyd, ; King, Lambert, Buonaccorsi, & Prout, ; Lambert, King, Buonaccorsi, & Prout, ; Studds, McFarland, et al, ), including state‐level extirpation of high‐elevation endemic species (Rimmer & Mcfarland, ). Moreover, in the White Mountains of New Hampshire, low‐elevation birds have been shown to have shifted their range over 100 m upslope while high‐elevation birds have shifted their ranges downslope over the same 19 year period (DeLuca & King, ).…”
Section: Introductionmentioning
confidence: 99%
“…During the study period, in New Hampshire (1993Lambert et al 2008), an annual decline (-7%) was reported while recent analyses from data across its United States range (2011-2016) produced a nonsignificant decline (Hill and Lloyd 2017). Bicknell's Thrush numbers were declining in the Canadian Maritimes and southeastern Québec where the species became extirpated from several locations (Whittam 2015, Québec Breeding Bird Atlas 2018.…”
Section: Discussionmentioning
confidence: 97%
“…Without discontinuing efforts to conserve breeding habitat, greater attention should be paid to other potential limiting factors. Current challenges for the species outside the breeding range are habitat loss and degradation due to anthropogenic and natural causes on its wintering grounds in the Greater Antilles (Hill and).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bicknell's Thrush (Catharus bicknelli) is a rare, range-restricted songbird, breeding only in high-elevation fir (Abies balsamea) forests of the northeastern United States and southeastern Canada and wintering predominantly in wet, broadleaf primary forests of the Dominican Republic (Townsend et al 2015). With a recent global population estimate of < 120,000, Bicknell's Thrush likely have one of the smallest population sizes of any regularly occurring migratory songbird species within the contiguous U.S. and Canada (Hill and Lloyd 2017), and is considered one of the Nearctic-Neotropical migrants at greatest risk of extinction and thus of highest continental conservation concern (Rich et al 2004, Wells 2007, Townsend et al 2015. In the northeastern U.S., 95% of the breeding population is found above 805 m elevation in naturally fragmented "sky islands" of montane fir forest (Hill and Lloyd 2017).…”
Section: Introductionmentioning
confidence: 99%